2018
DOI: 10.1186/s13046-018-0968-z
|View full text |Cite
|
Sign up to set email alerts
|

RBMS2 inhibits the proliferation by stabilizing P21 mRNA in breast cancer

Abstract: BackgroundRNA binding proteins (RBPs) play an important role in regulating the metabolism of target RNAs. Aberrant expression of RBPs plays a vital role in the initiation and development of many cancers. The RBM family, which has the conserved RNA binding motif RNP1 and RNP2, shares the similar function in RNA processing and RBMS2 is a member of them. P21, also named CDKN1A, promotes cell cycle arrest and plays an important role in halting cell proliferation. In our study, we identified RBMS2 as a tumor suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 33 publications
(35 reference statements)
4
37
0
Order By: Relevance
“…Furthermore, silencing HOXA-AS2 signi cantly downregulated the expression of EZH2 and upregulated the expression of P21. As an important regulatory factor of cell cycle, P21 protein is closely related to many kinds of cancer occurrence and development (24,25). We speculate that HOXA-AS2 may affect the tumor growth by regulating the expression of EZH2, but the speci c mechanism of HOXA-AS2 in OSSC remains to be studied further.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, silencing HOXA-AS2 signi cantly downregulated the expression of EZH2 and upregulated the expression of P21. As an important regulatory factor of cell cycle, P21 protein is closely related to many kinds of cancer occurrence and development (24,25). We speculate that HOXA-AS2 may affect the tumor growth by regulating the expression of EZH2, but the speci c mechanism of HOXA-AS2 in OSSC remains to be studied further.…”
Section: Discussionmentioning
confidence: 89%
“…All these results strongly supported that RBM7 acted as an oncogenic role in breast cancer. It was previously found that two other RBMs, RBM38 and RBMS2 acted as tumor suppressor in breast cancers 19 , 22 . Yang et al also found RBMS3 could inhibit breast cancer proliferation and metastasis 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…It was also linked with breast cancer epithelial-to-mesenchymal transition induced by TGF-β via stabilizing zonula occludens-1 mRNA 19 . We also identified another RBP, RBMS2, to stabilize the mRNA of P21 in breast cancer and thereby enhance its regulation 22 . However, the role of RBM7 in cancers, especially in breast cancer, is still unknown.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…P21, also known as CDKN1A which resided in 6p21.2 20,21 , has been investigated involvement in cell cycle regulation, differentiation, cell migration, cytoskeletal dynamic, apoptosis, transcription, DNA repair, induction of totipotent stem cells, autophagy and senescence 22,23 . Commonly accepted is that P21 as a member of cyclin-dependent kinase inhibitors (CDKI) interacts with various cell cycle proteins to mediate G1/S growth phase arrest in response to different stimuli 24,25 .…”
Section: Discussionmentioning
confidence: 99%